UPAYA MENINGKATKAN KETERAMPILAN BERHITUNG DENGAN MEDIA FLASH CARD ANAK DI PAUD CIKAL CILEGON - Asmayawati Asmayawati (LPPM Universitas Bina Bangsa, 2024)
The aim of this research is to find out whether the use of flash cards can improve simple arithmetic skills in young children. The subjects of this research were group A children aged 4-5 years at PAUD Cikal Cilegon. Class activity intervention planning includes 1) planning, 2) action, 3) observation, 4) reflection, then continued with the next cycle, namely planning, action, observation and reflection and so on. Based on the results of preliminary research data analysis, the percentage obtained was 47.39%, while in cycle I it was 71.87%. Based on this data, the percentage from pre-test to cycle increased by 24.48 percent for each indicator